Macroeconomic factors and stock index: investigation on commercial bank’s performance / Mohamad Zahin Sabri and Nur Syazwani Md Lazim - Sabri, Mohamad Zahin; Md Lazim, Nur Syazwani (Faculty of Business and Management, 2014)
This research is conduct to carry out the “Macroeconomic factors and stock index: Investigation on Commercial Bank’s performance”. In order to investigate the differ findings from other previous researcher, we have decided the relationship between external factors and commercial banks performance. The objectives of this research are to identify the determinants of commercial bank’s performance and to examine the relationships between the macroeconomics variables and stock index with the commercial bank’s performance as well as to determine the most significant determinants that influencing the performance of commercial banks. Our research provides quarterly data of commercial banks and macroeconomics variables from 1995 to 2013. We are measure the performance of the banks using Tobin Q method, consumer price index, base lending rate and KLCI Index. As results, we found that KLCI index have a positive and significant relationship with commercial banks performance whereas inflation and interest rate have an inverse relationship with commercial banks performance.